Analysis of swimming races in the 1989 Pan Pacific Swimming Championships and 1988 Japanese Olympic Trials - Wakayoshi, K.; Nomura, T.; Takahashi, G.; Mutoh, Y.; Miyashito, M. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
The purpose of this study was to determine the velocities (V) associated with the start phase, turn phase and stroke phase in the 100 m and 200 m swimming races, and to investigate the relationship between V, the stroke frequency (SF) and stroke length (SL) during the stroke phase. Swimming performances were analysed in the Pan Pacific Swimming Championships of 1989 and the 1988 Japanese Olympic Trials. The results of this study suggest that the swimmer's ability may be evaluated by determining the SF, SL and V of the three phases in the swimming races.